Pertumbuhan dan Produksi Tiga Varietas Sawi (Brassica juncea L.) Hidroponik Sistem NFT Pada Konsentrasi Nutrisi AB Mix yang Berbeda - Pamela Putri, Veren; Wahyuni, Endang Sri (Program Studi Agroteknologi, 2024)
This study aims to determine the most appropriate concentration of AB mix nutrients for the growth and production of three varieties of mustard greens, and to obtain the effect of different concentrations on the growth and production of three varieties of mustard greens (Brassica Juncea L.) hydroponic NFT system. This research was conducted at the Greenhouse Jl. BaturradenKecamatanSumbersari, Jember Regency, East Java from December 1 2020 to January 4 2021. The research design used was a two-factor factorial Completely Randomized Design (CRD) with 5 replications. The first factor is the concentration of AB mix nutrients (N) consisting of two treatment levels, N1 800 - 1200 ppm and N2 1000 - 1400 ppm. The second factor is the mustard variety (V) which consists of three mustard varieties, Pakcoy Sawi (V1), Caisim Sawi (V2) and Samhong Jade Sawi (V3). The data obtained was then analyzed with the F test using SPSS 24 for Windows software at the 0.05 level. The results showed that the AB mix nutrient concentration (1000-1400) ppm gave the best response to the parameters of root length and chlorophyll content, while the concentration (800-1000) ppm responded best to the parameters of plant height, number of leaves, root weight and fresh weight. The samhong jade mustard variety provided higher growth and production than pakcoy mustard greens in the observation parameters of plant height, number of leaves, root length, chlorophyll content and root weight. The best interaction between the nutrient concentrations of the AB mix mustard variety is the concentration (1000-1400) ppm with the Samhong jade variety (N2V3) on all observation parameters.